The Influence of Self-Control and Financial Attitude on the Financial Management Behavior of Shopee Paylater Users - Oetama, Seanewati; Susanto, Hari; Alejandra Kristiono, Kezia (Publisher Cv. Inara, 2025)
This study is entitled